Effectiveness of Project Based Learning Model in Learning Evaluation Course in Physics Education Study Programme - Parno Sumanro Mahulae; Tineke Makahinda; Patricia Mardiana Silangen; Alfrie Musa Rampengan (Postgraduate, University of Mataram, 2023)
The use of project-based learning model in learning can improve the quality of learning and students' learning outcomes. The purpose of this study was to determine how effective the project-based learning model is on learning outcomes.Â The method used in this research is quasi-experiment with one group pretest-posttest design. This research instrument is in the form of a student learning outcomes test in the form of descriptions, from the test results the n-gain test is carried out. The results showed an increase in student learning outcomes with an average pretest score of 45.73 and an average posttest score of 82.08. The result of the n-gain analysis is 0.57 which shows a moderate effectiveness category. Therefore, learning evaluation courses using project-based learning models is effective on student learning outcomes